2012
DOI: 10.1096/fj.12-214924
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of co‐ and post‐translational myristoylation of proteins during apoptosis: interplay ofN‐myristoyltransferases and caspases

Abstract: Myristoylation occurs cotranslationally on nascent proteins and post-translationally during apoptosis after caspase cleavages expose cryptic myristoylation sites. We demonstrate a drastic change in the myristoylated protein proteome in apoptotic cells, likely as more substrates are revealed by caspases. We show for the first time that both N-myristoyltransferases (NMTs) 1 and 2 are cleaved during apoptosis and that the caspase-3- or -8-mediated cleavage of NMT1 at Asp-72 precedes the cleavage of NMT2 by caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…Among these genes, mTOR, CTDSPL and SMARCA5 have been previously identified and experimentally confirmed as functional targets for miR-99 family members [5], [7], [11], [34], [35]. HOXA1 is a known oncogene [36][40], and NMT1 also plays a role in regulating tumor cell proliferation and apoptosis [41], [42]. TMEM30A plays a major role in cell polarity control and microtubule regulation, and is also involved in cell migration [43].…”
Section: Resultsmentioning
confidence: 99%
“…Among these genes, mTOR, CTDSPL and SMARCA5 have been previously identified and experimentally confirmed as functional targets for miR-99 family members [5], [7], [11], [34], [35]. HOXA1 is a known oncogene [36][40], and NMT1 also plays a role in regulating tumor cell proliferation and apoptosis [41], [42]. TMEM30A plays a major role in cell polarity control and microtubule regulation, and is also involved in cell migration [43].…”
Section: Resultsmentioning
confidence: 99%
“…Lipid modification serves to target many proteins to specific membranes or submembrane locations. Hundreds of proteins are known to be modified with covalently bound lipid groups, the most common of which are fatty acids, isoprenoids, and glycosylphosphatidylinositol anchors (Farazi et al, 2001; Jeromin et al, 2004; Perinpanayagan et al, 2013; Resh, 2006; Steinhauer and Treisman, 2009). Many of these proteins are involved in signaling, and require membrane association to signal efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the obvious importance of acylated proteins in biology (e.g., kinases and phosphatases (Kim et al, 2009; Resh, 2006; Schlessinger, 2000), G proteins (Resh, 2006), GPCRs (Resh, 2006), morphogens (Steinhauer and Treisman, 2009), neuronal calcium sensors (Jeromin et al, 2004), pro- and anti-apoptotic proteins (Perinpanayagan et al, 2013)), standard approaches for studying their structure at membranes are neither adequate nor appropriate. In addition, understanding signaling mechanisms involving these proteins at the molecular level and developing pharmaceutical interventions has been limited by the absence of structural detail for these proteins in the membrane-bound state.…”
Section: Introductionmentioning
confidence: 99%
“…[12] NMT is constituted by a saddle-shaped b sheet motif flanked by a helices, displaying pseudo-twofold symmetry with regions corresponding to the N-and C-terminal portions of NMT. [17] Perinpanayagam et al [18] reported NMT-1 to be a substrate of caspases-3 and -8, whereas NMT-2 is a caspase-3 substrate only. [13] NMT is a member of the GNAT superfamily of proteins, which was first identified in Saccharomyces cerevisiae by Towler, Glaser, and colleagues via the N-terminal sequence (Gly-Asn-Ala-Ala-Ala-Ala-Arg-Arg) of the catalytic subunit of cAMP-dependent protein kinase.…”
Section: Introductionmentioning
confidence: 99%
“…NMT-1 was reported to be present in four distinct isoforms, ranging from 49 to 68 kDa, whereas only a single NMT-2 isoform (65 kDa) was found. [17] Perinpanayagam et al [18] reported NMT-1 to be a substrate of caspases-3 and -8, whereas NMT-2 is a caspase-3 substrate only. Meanwhile, the cleavage sites located at the N termini of both NMTs was identified as well.…”
Section: Introductionmentioning
confidence: 99%